Recycle glass waste as a host for solidification of oil sludge - Nur Syuhada Izzati Ruzali; Syazwani Mohd Fadzil; Um, Wooyong; Mohd Idzat Idris; Rohyiza Ba’an (Penerbit Universiti Kebangsaan Malaysia, 2022)
The production of oil sludge per year is more than 1 billion tonne that mainly generated from the production, refinery, storage, and transportation of petroleum. Disposal of oil sludge had been a great issue since the waste consists of highly concentrated of Natural Occurring Radioactive Material (NORM). Therefore, to overcome this problem, this study aims to investigate used and recycle borosilicate glass as a host for solidification of oil sludge. The oil sludge and glass host were mixed into different compositions, melted at high temperature (1,100 °C -1,200 °C) for 1 h in alumina crucible and rapidly cooling in the room temperature, by reducing the radioactivity levels of NORM. This study found out that, the optimum waste loading was obtained at a range of 20-25 wt% of oil sludge and 75-80 wt% of the glass host at 1,200 °C. All the glass waste was produced as an amorphous phase material with small amount of crystalline phase such as SiO2, Ba4-Al2-O7, AlPO4, Al2O3 and Fe3Zn10, which observed to be appeared during the cooling process. The major elements of the glass waste were found to be distributed uniformly based on energy dispersive X-ray spectroscopy (EDX) mapping. Furthermore, the dissolution rate of indicator element increased due to the increase of pH solution, while the normalized releases of B, Si, and Na during product consistency tests were low and below the standard glass limit, which shows high durability of the glass due to lower release of glass elements. Therefore, this study emphasized the suitability of recycle borosilicate glass as a host for immobilization of oil sludge prior for disposal, while deploying high temperature technology.